(untitled) - Porter, Patricia A. (Boston, MA, 1992)
The second edition of Communicating Effectively in English presents a highly interactive, experiential format for developing stronger speaking and listening skills in a variety of contexts - interpersonal, small group, and large group. Many activities, examples, and assignments helps students sharpen their interview, discussion, and public speaking skills. As they progress from simpler informative speeches to more complex persuasive speeches, students learn to how to consider the interests of the audience, how to choose appropriate topics, how to organize and support their ideas, and how to prepare effective introductions and conclusions
Keywords: English language,Oral communication; Textbooks for foreign speakers